TATA LAKSANA PENDARATAN IKAN DAN ANTRIAN KAPAL DI PELABUHAN PERIKANAN PANTAI MAYANGAN - Made Mahendra Jaya; Liya Tri Khikmawati; I Putu Yoga Iswara Putra (Jurnal Teknologi Perikanan dan Kelautan, 2022)
Mayangan costal fishing port is one of the fishing port for fisheries activities in Probolinggo. This port has many facilities such as fish market, ice factory, easy road access, and other facilities. Those facilities are able to serve or support fishing vessels activities. The purpose of this study were to find the fish landing process and ship queue handling in Mayangan fishing port. This study was a descriptive and used a case study method. Primary data gathered were function and facilities in Mayangan fisihing port. The result showed that Mayangan fishing port had 3 docks (jetty, landing, and sheet pile). Jetty was only use for anchored only. The process of unloading fish on landing dock was when the ship came to the port and anchored. After anchored, the process of unloading catches begin using baskets from bamboo then brought to fish auction by the crews or fish pickers. On sheet pile the unloading fish assisted by a slide made of wood. The fish unloaded from the ship with a slide and then it put into a plastic basket, then brought to fish auction or directly transported by car for sale immediately. During the loading and unloading process, the fish confdition was always to be kept in the fish fresh condition. The ship queuing system at Mayangan fishing port used a single line multiple stage queuing system (single channel multi server).